ISSUES OF IMPLEMENTING ARTIFICIAL INTELLIGENCE IN HUMAN RESOURCE MANAGEMENT IN UZBEKISTAN - Latipov Ashur Ali; Hamrayev Abdulkhofiz (Ecomind Press, 2025)
The article titled "The Issues of Implementing Artificial Intelligence in Human Resource Management in Uzbekistan" examines the current state and prospects of utilizing artificial intelligence (AI) in the management of human resources in Uzbekistan. The article discusses the key challenges and opportunities for integrating AI into HR processes, focusing on its potential to enhance decision-making, streamline recruitment, and optimize workforce management. The study also highlights the importance of developing a regulatory framework and the need for training and upskilling HR professionals to adapt to emerging technologies. Additionally, the article provides an analysis of global best practices and how they can be applied within the context of Uzbekistan's evolving economy. The findings emphasize that AI can play a significant role in improving the efficiency and effectiveness of human resource management, contributing to the overall development of the country's workforce in the context of digital transformation.
Keywords: Artificial intelligence, human resource management, HR management, innovative technologies, digital transformation, workforce management, personnel policy, automation, data analytics, technological development, personnel management.